The Evaluatıon Of Relatıonshıp Of Mandıbular Thırd Molar Wıth Skeletal Maturıty And Chronologıcal Age - Jalan Devecioğlu Kama; Orhan Hamamcı; Semra Özer (Galenos Yayinevi, 1997)
To evaluate the relationship of mandible third molar, chronological age and skeletal maturity, this study was done an 250 individuals with 10-24 years old. A correlation was observed between chronological age, skeletal maturity and mandibular third molar.